Internationalization of the competition law - Šćepanović Nina (Međunarodni Problemi)
In the present stage of development of international economic relations multilateral regulation of competition is becoming more and more important in order to, firstly, annul the effects of domestic rules of competition that are today considered the greatest non-tariff limitation, secondly avoid conflicts that can be caused by exterritorial implementation of national rules in this field, and, finally, define the rules of behavior in the world market. Although the first attempts to regulate this field were made pretty long ago and some activities were taken within UNCTAD, OECD and GATT, no comprehensive rules considering the issues they define and a group of countries that implement them have been adopted at the international level, so far. For the time being, numerous competition problems in relations among countries have been overcome by concluding a number of bilateral agreements and several regional arrangements.